Bankruptcy Technology, Finance, and Entrepreneurship - Sobrinho, Nelson (IMF Working Papers; Working Paper ;, 2017)
Using an overlapping-generations growth model featuring financial intermediation, I find that inefficiencies in technology to deal with private debt distress (bankruptcy technology), and obstacles to entrepreneurship (high costs of doing business) have significant negative effects on the income per capita and welfare of developing countries. These inefficiencies may also interact in perverse ways, futher amplifying the negagtive effects in the long run. The results provide strong rationale for structural reforms that simultaneously speed up the resolution of private sector insolvency, improve creditor protection, and eliminate obstacles to entrepreneurship.